Heroism in Doctor Who 1963 - 2020 - Hardt, Maria-Xenia (HELDEN - HEROISIERUNGEN - HEROISMEN, 2022)
This study of the heroic in Doctor Who offers a look at the underlying sociocultural make-up of Great Britain through the course of more than half a century, combining experiences of the day-to-day and grand national narratives due to the ways in which the medium of television is embedded in cultural sense-making. The heroes of Doctor Who are woven into the everyday - discussed over dinner, argued about in coffee breaks and on social media, and peering out from posters in childhood bedrooms. Yet the heroes are exceptional in ways that exceed the realm and reach of the viewers' every-day. They are always in motion. They travel to the edge of time. They negotiate the values, identities and feeling-states of whole generations of the British nation.